2008
DOI: 10.1021/op700225u
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Microwave-Assisted Reaction Optimization and Scale-Up Using Fluorous Spacer Technology

Abstract: Microwave-assisted organic synthesis in a laboratory-scale monomodal microwave reactor is investigated for continuous flow applications using fluorous spacer technology. The benchtop continuous flow microwave described allows sequential processing of multiple plugs using small amounts of reagents for reaction optimization, scale-up and array synthesis. The system features online monitoring of temperature, pressure and microwave power. Several different reactions have been scaled up, including a Suzuki-Miyaura … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…These principles were demonstrated with α‐diazo‐β‐keto ester synthesis and a nucleophilic aromatic substitution reaction, albeit with far larger droplet volumes (>100 μL) than used in non‐industrial applications of droplet‐based synthesis 186. Using perfluoromethyldecalin (PFMD), a low‐microwave absorber, as a carrier phase, the group also showed that microwave technology can be applied to Suzuki–Miyaura cross‐coupling and nucleophilic substitution reactions in droplets 187…”
Section: Small‐molecule Synthesis In Dropletsmentioning
confidence: 99%
“…These principles were demonstrated with α‐diazo‐β‐keto ester synthesis and a nucleophilic aromatic substitution reaction, albeit with far larger droplet volumes (>100 μL) than used in non‐industrial applications of droplet‐based synthesis 186. Using perfluoromethyldecalin (PFMD), a low‐microwave absorber, as a carrier phase, the group also showed that microwave technology can be applied to Suzuki–Miyaura cross‐coupling and nucleophilic substitution reactions in droplets 187…”
Section: Small‐molecule Synthesis In Dropletsmentioning
confidence: 99%
“…d K represents the combination of k variables varied 2 or 3 at a time while the remaining (k−2) or (k−3) is kept at the 0 level. [14]. The work showed the advantages of using an immiscible fluorinated spacer (perfluromethyldecalin, PFMD) for the formation of discrete reaction plugs in the system.…”
Section: Central Composite Designmentioning
confidence: 99%
“…Many devices are highly portable, being hand-held or even smaller in size, allowing rapid reconfiguration and minimising the impact on an experimental setup. Specialist devices can operate beyond the normal visible regions, providing for instance near-IR imagery for low-light situations or IR thermal imagery for monitoring exothermic events and microwave chemistries [3941]. Such equipment usually comes at a significantly increased cost.…”
Section: Reviewmentioning
confidence: 99%